ANALYSIS OF RAINFALL EROSIVITY INDEX USING THE BOLS AND LENVAIN METHODS (Malaysian Journal of Civil Engineering, 2023)
Indonesia has a tropical climate, which causes variations in the intensity of rainfall. With a high level of rainfall intensity, Indonesia is vulnerable to. The ability of to cause erosion is called erosivity. The aim of the study was to determine the rain erosivity index as a potential erosion control plan. The employed methods were the Bols and Lenvain methods involving the rainfall consistency test, analysis of average rainfall, and analysis of the erosivity index of rain. The results indicate that only Penengahan Station was eligible for the rainfall analysis with determination coefficient values (R2) of 0.9904 and 0.9889 with the Bols and Lenvain methods respectively. The annual average erosivity index value with the Bols method was 1762.23, while with the Lenvain method, it was 1280.19. With the results in mind, it is safe to infer that the use of the Bols equation is safer to apply to a plan concerning erosion potential mitigation caused by rainfall in the sub-sub watershed area of Khilau as the Bols method yielded a larger value.